2022
DOI: 10.3390/environments9100131
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Spatial and Temporal Trends of Microplastic Pollution in Surface Water and in the Eastern Oyster Crassostrea virginica for a Dynamic Florida Estuary

Abstract: Microplastics (MPs) are a ubiquitous pollutant, emphasizing the need to understand their abundance and the factors that influence these patterns around the globe. In a prior study, high numbers of MPs were found in surface waters and tissues of the oyster Crassostrea virginica collected from one location in the Indian River Lagoon (IRL, FL, USA). To better understand spatial and temporal variability of MPs throughout the IRL, for one year, monthly surface water samples were collected from 35 sites, while oyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…It is interesting that the mean density (0.53 MP/L) was lower than that found by Walters et al [48] of 1.47 ± 0.09 MP/L. This difference may be the result of the collection locations.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…It is interesting that the mean density (0.53 MP/L) was lower than that found by Walters et al [48] of 1.47 ± 0.09 MP/L. This difference may be the result of the collection locations.…”
Section: Discussioncontrasting
confidence: 53%
“…Weather conditions may have also impacted the results, especially fall storms where both projects reported the highest MP densities. Major Hurricane Dorian (Category 5) in September 2019 and multiple tropical storms occurred during the study by Walters et al [48], while Hurricanes Sally (Category 2) in September 2020 and Elsa (Category 1) in July 2021 occurred in Florida during the present study. The month of October had the overall highest number of MPs, followed by September.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…A study conducted on edible oysters reported the translocation and accumulation of MPs in the gills, muscles, and digestive glands [ 23 ]. Adult Eastern oysters are sedentary and grow attached to the seabed near the shoreline in intertidal regions, where they are exposed to MPs that are sinking or caught in the biofilm [ 24 ]. A few laboratory studies have been conducted on the impacts of MPs on Pacific oyster ( Crassostrea gigas ) larvae: A previous study found that Pacific oyster larvae can ingest polystyrene particles of less than 20 µm without any significant impact on their development and feeding capacity [ 25 ]; A research conducted on reproductively active Pacific oyster adults and their offspring and reported a decrease in the size and growth of larvae due to polystyrene exposure and a significant decrease in oocyte number and oocyte quality [ 26 ].…”
Section: Introductionmentioning
confidence: 99%